2006
DOI: 10.1007/s00442-006-0569-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the herbivorous minnow, southern redbelly dace (Phoxinus erythrogaster), on stream productivity and ecosystem structure

Abstract: We used field and mesocosm experiments to measure effects of southern redbelly dace (Phoxinus erythrogaster), a grazing minnow, on stream ecosystem structure and function. Ecosystem structure was quantified as algal filament length, algal biomass, size distribution of particulate organic matter (POM), algal assemblage structure, and invertebrate assemblage structure, whereas ecosystem function was based on gross and net primary productivity. Our experiments showed that moderate densities of Phoxinus temporaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 59 publications
(58 reference statements)
4
42
1
Order By: Relevance
“…Our mesocosm results were consistent with a weak dace effect on recovery of adnate, diatomdominated algal assemblages in Kings Creek after a flood (Bertrand et al 2009). Dace effects in mesocosms were weak but consistent with previous findings for effects of stream grazing fish that included decreased algal biomass, filament lengths, and benthic particle size (Power and Matthews 1983, Power et al 1988b, Bertrand and Gido 2007 and increased biomassspecific GPP (Gelwick and Matthews 1992). Moreover, attenuation of grazer influence also is consistent with results from Gelwick and Matthews (1992), who measured the effects of central stoneroller (Campostoma anomalum) over time.…”
Section: Dace Role After Floodsupporting
confidence: 79%
See 1 more Smart Citation
“…Our mesocosm results were consistent with a weak dace effect on recovery of adnate, diatomdominated algal assemblages in Kings Creek after a flood (Bertrand et al 2009). Dace effects in mesocosms were weak but consistent with previous findings for effects of stream grazing fish that included decreased algal biomass, filament lengths, and benthic particle size (Power and Matthews 1983, Power et al 1988b, Bertrand and Gido 2007 and increased biomassspecific GPP (Gelwick and Matthews 1992). Moreover, attenuation of grazer influence also is consistent with results from Gelwick and Matthews (1992), who measured the effects of central stoneroller (Campostoma anomalum) over time.…”
Section: Dace Role After Floodsupporting
confidence: 79%
“…Densities were based on the range that typically occur in nearby Kings Creek (Franssen et al 2006, Bertrand andGido 2007) and are similar to densities reported for this species in other prairie streams (Stasiak 2007). Each dace density treatment was replicated once at each nutrient concentration, and combinations of nutrient and density treatments were assigned randomly to mesocosms.…”
Section: Experimental Designmentioning
confidence: 81%
“…Three filaments were measured per transect to give 9 measurements in the riffle and 9 in the pool of each mesocosm (Bertrand and Gido 2007, Bengtson et al 2008. Maximum filament length was used to determine the greatest attainable biomass under the treatment conditions while minimally disturbing the benthic community and to remain consistent with earlier studies (Bertrand and Gido 2007). Mean filament length was calculated for each stream pool and riffle separately (i.e., the mean longest filament in a riffle or pool was the response variable).…”
Section: Ecosystem Structurementioning
confidence: 99%
“…In many studies of the effects of consumers (e.g., grazing fishes) on ecosystems, only structural but not function were measured (i.e., relative biomass, not material and energy fluxes; e.g., Cardinale et al 2006 used biomass as the response variable and did not take productivity into account in a meta-analysis), even though multiple pathways exist for consumers to influence both structure and function. Grazing fishes have the potential to affect stream N removal, an important ecosystem function, by increasing N supply , altering algal nutrient demand (Flecker et al 2002), and reducing particulate organic matter (POM) size (Bertrand and Gido 2007). Reduced particle size directly increased denitrification in aquifer microcosms (Dodds et al 1996b).…”
mentioning
confidence: 99%
See 1 more Smart Citation